Hakikat tafsir menurut mufasir dan sejarahnya - Fayyahd, Muh (Maliki Interdisciplinary Journal, 2025)
Tafsir is a discipline for explaining the contents of the Koran, describing the conversation between the text of the Koran and dynamic life problems. The level of understanding of the Koran depends greatly on the expertise of the exegetes, which creates a more religious meaning along with a high level of knowledge. The Koran contains a variety of Islamic knowledge and is considered a guide for Muslims. Tafsir is carried out to understand the secrets of the Koran, and academics continue to interpret it to this day. The depth of understanding of Al-Quran scholars encourages them to work together in understanding the meanings of the Al-Quran which continues to change with the times. Tafsir is carried out using scientific studies, involving Al-Quran experts and other scientific knowledge, as carried out by the Ministry of Religion’s Lajnah Tashih Al-Quran Team. This research aims to find out and understand more deeply the nature of interpretation according to interpreters and its history. The method used in the research is the scientific work review method using a theoretical approach to analyze and evaluate the contribution of book chapters or journal articles to existing theoretical understanding. The results of this research show that tafsir is understood as an interpretation of the Al-Qur’an which reveals the meaning of its words. The Companions used the riwayah method in interpreting the Qur’an, except for a few verses that require ijtihad interpretation. Various schools of interpretation and interpretation techniques have developed since the time of the Prophet Muhammad SAW until now. Tafsir schools in Mecca, Medina and Iraq during the tabi’in period marked the development of tafsir. The tadwin phase experienced the development of tafsir as evidenced by the emergence of tafsir books. The maudhui method used by mufassir, including Indonesian mufassir, marks the end of the codification period and the beginning of the modern era in the interpretation of the Qur’an which has undergone significant changes.